Advances in System Optimization and Control Select Proceedings of ICAEDC 2017 - Singh, Sri Niwas; Wen, Fushuan; Jain, Monika; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book comprises select proceedings of the International Conference on Advancement in Energy, Drives, and Control. It covers frontier topics in optimization and control. It covers applications of optimization processes in areas such as computer architecture, communication systems, system optimization, signal processing, fluid dynamics and process control. This book is of use to researchers, professionals, and students from across engineering disciplines.
Maximum Power Point Tracking approaches for Wind-Solar Hybrid Renewable Energy System: A Review -- Short Term PV Power Forecasting Using Generalized Neural Network and Weather Type Classification -- Model Order Reduction of Two Area Hydro Plant using Mixed Method -- Current Trends in Control Techniques in Renewable Energy: A Review -- Performance Analysis of PV Cell Using One-Diode and Two Diode Model -- Active Power Regulation by MPC based Flywheel Energy Storage System -- Post evaluation Index System and Comprehensive Evaluation Method for Daily Power System Dispatching -- Real Assessment of State owned Indian Electric Utilities -- A Novel Scheme of Fault Detection in Power Transmission Line Using Image Processing -- Power Quality Improvement of Power Distribution System Under Symmetrical and Unsymmetrical Faults Using D-STATCOM -- Optimal sitting and sizing of capacitor using iterative search method for enhancement of Reliability of Distribution System -- Battery Energy Storage Technology Integrated For Power System Reliability Improvement -- Thermal Evaluation and Oxidation Stability of High Temperature Alternative Solid Dielectrics of Power Transformers in Mixed Oil -- Multi-Area Economic Dispatch Using Dynamically Controlled Particle Swarm Optimization -- An Analytical Hierarchy Process based approach for Effective Maintenance Prioritization of Power Transformers -- Designing of Controllers using Chebyshev-Pole Clustering Approximants -- Comparison: Matrix Converter, Cycloconverter and DC Link Converter -- Power Quality Improvement and Analysis Using Multi-pulse Converters.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Electric power production; Security systems; Multibody Systems and Mechanical Vibrations; Electrical Power Engineering; Security Science and Technology